2009
DOI: 10.1210/jc.2008-2049
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Study of Thyroid Cancer and Other Thyroid Diseases among Individuals Exposed in Utero to Iodine-131 from Chernobyl Fallout

Abstract: Our results suggest that in utero exposure to radioiodines may have increased the risk of thyroid carcinoma approximately 20 yr after the Chernobyl accident, supporting a conservative approach to medical uses of I-131 during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 24 publications
0
45
1
2
Order By: Relevance
“…In Ukraine, there are extensive risk analyses of thyroid cancer and of other thyroid diseases among individuals exposed in utero to 131 I from Chernobyl fallout [54] as well as of that of non-cancer thyroid neoplasms [55] and autoimmune thyroiditis [56]. The results of this large-scale project are expected to further refine conclusions of the earlier, concurrent and ongoing studies.…”
Section: Major Medical and Epidemiological Studies Of The Chernobyl Amentioning
confidence: 82%
“…In Ukraine, there are extensive risk analyses of thyroid cancer and of other thyroid diseases among individuals exposed in utero to 131 I from Chernobyl fallout [54] as well as of that of non-cancer thyroid neoplasms [55] and autoimmune thyroiditis [56]. The results of this large-scale project are expected to further refine conclusions of the earlier, concurrent and ongoing studies.…”
Section: Major Medical and Epidemiological Studies Of The Chernobyl Amentioning
confidence: 82%
“…In a previous study, we investigated the radiation-related risk of thyroid diseases in a cohort of adolescents who were in utero at the time of the Chernobyl accident in Ukraine. We found a nonsignificant increase in risk for thyroid cancer, but not for other thyroid diseases, with in utero I-131 dose (EOR/Gy = 11.66; P = 0.12) (21). …”
Section: Introductionmentioning
confidence: 75%
“…Details of the study design, population and recruitment have been reported previously (21) and are described briefly here. Eligible mothers had to be pregnant at some point during the time period April 26, 1986 to June 30, 1986, had a live birth resulting from the pregnancy, and a mailing address in one of three northern oblasts (provinces) of Ukraine that were contaminated as a result of the Chernobyl accident.…”
Section: Methodsmentioning
confidence: 99%
“…A study of thyroid cancer among individuals exposed in utero to I 131 from Chernobyl fallout demonstrated an increased risk of thyroid carcinoma about 20 years after the accident. 7 Utiger stated that even maternal thyroid deficiency during the latter two thirds of gestation could result in mental retardation and sometimes neurologic deficits. 8 Although in utero fetal thyroid replacement therapy has been reported, termination of pregnancy was performed due to the increased risk of subsequent malignancy as well as a possible impairment of brain development, which might have already occurred during the time of presentation due to the time interval between radioactive iodine exposure and the diagnosis.…”
Section: Discussionmentioning
confidence: 99%